Realization of Looking up Virtual Router's FIB Based on Set Partition - Ying Hu; Lei Zhuang (Dianxin kexue)
Virtual router is a core network device of future internet, which runs multiple virtual routers in parallel on a common physical router platform. It is aimed at the looking up technology on virtual router's forwarding table, which using the way of set partition to cut apart the prefixes set into two sets that realized using SRAM and DRAM respectively. Various solutions were analyzed, and new method that to use mark bit solving the problem of inefficient looking up overlapping prefixes in SRAM, was proposed. The experiment results show that the solution greatly reduces storage space, and optimizes the overall effects.